Growth monitoring: testing the new guidelines. Issue 4 (1st October 1998) - Mulligan, J; Voss, L D; McCaughey, E S; Bailey, B J R; Betts, P R
Abstract : OBJECTIVE: To assess the impact of recent guidelines from the UK joint working party of child health surveillance recommending that all children be measured at age 5 and again between 7 and 9 years of age to determine how many normal school age children are likely to be referred for specialist assessment. METHODS: The longitudinal data of 486 children measured by school nurses in a community setting were examined and compared with measurements made in a research setting by a single, skilled observer. MAIN OUTCOME MEASURES: Number of children identified as having abnormal stature (< 0.4th or > 99.6th centile) and abnormal growth rate height standard deviation score (HSDS) change > 0.67). RESULTS: The community survey identified seven (1.4%) children as having abnormal stature (four short, three tall), 11 (2.3%) were identified as "slow growing", and nine (1.9%) increased their HSDS by more than 0.67. These results were comparable to data collected in ideal research conditions. CONCLUSIONS: Following the recommendations would not result in an excess number of inappropriate referrals. However, this study highlights several unresolved issues such as interobserver variablity and time interval between measurements. A large scale prospective study should be considered to establish realistic and cost-effective criteria before implementation of a national screening programme.